2017
DOI: 10.1016/j.impact.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanomaterial and media physicochemical properties on nanomaterial aggregation kinetics

Abstract: Understanding nanomaterial (NM) stability is required for an adequate interpretation of ecotoxicological test outcomes, fate and behavior studies, to generate parameters (such as critical coagulation concentration, CCC; and attachment efficiency, α) for environmental fate models, and for comparison among different studies. Numerous studies measured CCC and α for different types of NMs with a major focus on investigating the effect of ionic strength, ion valency and natural organic matter, with fewer studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 157 publications
(228 reference statements)
0
44
0
1
Order By: Relevance
“…Therefore, an additional mechanism of stabilization, besides the electrostatic one should be in action for silica nanoparticles, such as for example a shift of surface charges location to outside the solid/liquid interface and/or a steric repulsion of flexible protruding surface groups [74]. It was found that addition of electrolyte destabilizes silica nano-suspensions and CCC for monovalent salt (NaCl) was two orders of magnitude higher than that for divalent salts in good agreement with the Shulze-Hardy rule [75]. For the divalent salts however, ion-specific effect was observed: MgCl 2 has two times smaller CCC than CaCl 2 and BaCl 2 .…”
Section: Experimental Studies Of Nano-particle Interactionsmentioning
confidence: 52%
“…Therefore, an additional mechanism of stabilization, besides the electrostatic one should be in action for silica nanoparticles, such as for example a shift of surface charges location to outside the solid/liquid interface and/or a steric repulsion of flexible protruding surface groups [74]. It was found that addition of electrolyte destabilizes silica nano-suspensions and CCC for monovalent salt (NaCl) was two orders of magnitude higher than that for divalent salts in good agreement with the Shulze-Hardy rule [75]. For the divalent salts however, ion-specific effect was observed: MgCl 2 has two times smaller CCC than CaCl 2 and BaCl 2 .…”
Section: Experimental Studies Of Nano-particle Interactionsmentioning
confidence: 52%
“…As a result of the NP intrinsic (e.g., size, shape, roughness, and crystallinity) and extrinsic (e.g., temperature, ionic strength and composition, NOM) properties (Petosa et al, 2010;Baalousha, 2017), NPs may undergo rapid transformations in NSW, which drive NP fate and determine the presence (or absence) of effects on the marine biota (Matranga and Corsi, 2012;Corsi et al, 2014;Blasco et al, 2015).…”
Section: Np Fate and Behavior In Sea Watermentioning
confidence: 99%
“…Despite this wide industrial application of TiO 2 ‐NP, little attention has been given to the environmental impact of their disposal, and there is still no specific regulation for discarding nanomaterials into aquatic systems . In aqueous solutions, TiO 2 ‐NP tend to agglomerate/aggregate or interact with suspended organic matter, and then deposit on the sediment . However, some TiO 2 ‐NP remain suspended in the water column (52‐86 μgL −1 ), mostly near sewages .…”
Section: Introductionmentioning
confidence: 99%